ANALYSIS OF WORK CULTURE, WORKLOAD, AND JOB STRESS ON JOB SATISFACTION AND ITS IMPACT ON EMPLOYEE PERFORMANCE AT PT BANK OCBC SPACE BSD TANGERANG - Fajri Rahmadeli; Hamsinah Hamsinah; Agustina Mogi (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the influence of work culture, workload, and work stress on job satisfaction and their impact on employee performance at PT Bank OCBC Space BSD Tangerang. The background of this research is based on fluctuations in employee performance, suboptimal attendance levels, and inconsistent achievement of KPIs and service levels, which are presumed to be influenced by internal human resource factors. This research adopts a quantitative approach using a survey method. The population consists of all employees of PT Bank OCBC Space BSD Tangerang, with the sampling technique employing a census method. Data were collected through questionnaires using a Likert scale and analyzed using path analysis to examine both direct and indirect relationships among variables. The results indicate that work culture, workload, and work stress have a significant effect on job satisfaction. Furthermore, job satisfaction has a significant influence on employee performance and acts as an intervening variable in the relationship between work culture, workload, and work stress on employee performance. These findings suggest that improving employee performance can be achieved through the development of a positive work culture, proportional workload management, and effective control of work stress. This study is expected to provide managerial insights for formulating human resource management policies oriented toward enhancing job satisfaction and employee performance.